The 5Ps Model to Optimize Compression Athletic Wear Comfort in Sports (Journal of Fiber Bioengineering and Informatics, 2018)
Engineered design of compression athletic wear has been selectively applied in various recognized Olympic sports and popular recreational activities. This recent development is, as one type of additional body-behavioural support, protection and adjustment, plays a crucial role, in improving the athletes' performances. Typically, this is accomplished by providing engineered design support, pressure, and form-fit on targeted areas of athletes' body. In the present paper, a contextual model including 5Ps (i.e. Physical, Psychological, Physiological, Psychophysical, and Psychophysiological properties) related to user comfort and performance, has been developed to analyze multiple relationships between the athlete, athletic wear, immediate body space and sports environment, which would help us understand the effects of athletic wear on sports performance. The 5Ps reference model explores the mechanisms of action of body-clothing-environment system from a comprehensive view, thus effectively optimizing functional design of compression athletic wear in practice to enhance sports achievement and comfort.